2021
DOI: 10.1016/j.omto.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

A synDNA vaccine delivering neoAg collections controls heterogenous, multifocal murine lung and ovarian tumors via robust T cell generation

Abstract: Neoantigens are tumor-specific antigens that arise due to somatic mutations in the DNA of tumor cells. They represent ideal targets for cancer immunotherapy since there is minimal risk for on-target, off-tumor toxicities. Additionally, these are foreign antigens that should be immunogenic due to lack of central immune tolerance. Tumor neoantigens are predominantly passenger mutations, which do not contribute to tumorigenesis. In cases of multi-focal or metastatic tumors, different foci can have significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The creation of a successful therapeutic protocol that combines ICI and NCV is currently a work in progress. The induction of multi-epitopic and multi-functional immune responses by NCV was shown to be relevant in the MC38 tumor model 15 and other tumor models 31 , 41 . Here we extended this concept and explored the strength of DNA-EP platform confirming the immunogenicity of neoantigen previously used in other delivery systems or in the form of shorter coding sequencing (Tables 1 and 2 ).…”
Section: Discussionmentioning
confidence: 96%
“…The creation of a successful therapeutic protocol that combines ICI and NCV is currently a work in progress. The induction of multi-epitopic and multi-functional immune responses by NCV was shown to be relevant in the MC38 tumor model 15 and other tumor models 31 , 41 . Here we extended this concept and explored the strength of DNA-EP platform confirming the immunogenicity of neoantigen previously used in other delivery systems or in the form of shorter coding sequencing (Tables 1 and 2 ).…”
Section: Discussionmentioning
confidence: 96%
“…Since the development of multiepitope T cell memory appears to have an advantage over tumor recurrence, encoding several neoantigens-in this example, by a DNA vaccine-can be a beneficial tool for targeting heterogeneous multifocal or metastatic cancers. 104 To investigate the theory that ovarian cancer cells will express more class I MHC and cancertestis antigens (CTA) when their DNA methylation is reduced. 105 This will enhance the cells' capacity to be recognized by antigenreactive CD8+ T cells.…”
Section: Mrna-based Vaccinementioning
confidence: 99%
“…DNA has also used to produce neoantigen vaccines. Researchers have shown that synthetic DNA vaccines – recombinant plasmids that can produce neoantigens – can generate robust T cell responses in mice [85–87] . Another study indicated that combining DNA vaccination with anti-PD-1 therapy can achieve a synergistic effect in controlling tumor growth [88] .…”
Section: Clinical Applications Of Neoantigensmentioning
confidence: 99%
“…Researchers have shown that synthetic DNA vaccinesrecombinant plasmids that can produce neoantigenscan generate robust T cell responses in mice. [85][86][87] Another study indicated that combining DNA vaccination with anti-PD-1 therapy can achieve a synergistic effect in controlling tumor growth. [88] Their data suggest that a combination strategy of immunotherapies may bring about unexpected benefits.…”
Section: Therapies Based On Neoantigensmentioning
confidence: 99%